POLICY ON THE USE OF SOCIAL MEDIA IN HOSPITALS IN BUILDING COMMUNICATION DURING THE COVID-19 PANDEMIC: LITERATURE REVIEW - Kumalasari, Rita; Sulistiadi, Wahyu (UI Scholars Hub, 2022)
Social media is necessary for almost everyone, including in health services. During the COVID-19 pandemic, social media was widely used to build hospital communications. However, the benefits come with risks, as communication spreads so quickly. A proper policy is needed. This study aims to determine the benefits of social media in building communication in hospitals and the policies that govern it. The method used is a literature study. A literature search, through Science Direct, ProQuest, Google Scholar, and other databases (Google scholar, NIH/NLM, JMIH), with the keywords